PERAN CSR (CORPORATE SOCIAL RESPONSIBILITY) BANYAN TREE RESORT BINTAN DALAM MEMBANGUN KESEJAHTERAAN LINGKUNGAN MASYARAKAT LAGOI - KEPULAUAN RIAU - Gress, Lola Rotua; Achnes, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The aim of this research is discover (1) the role of CSR (Corporate Social Responsibility) Banyan Tree Resort Bintan in building prosperity of socialenvironmentcommunity LagoiKepulauan Riau; (2) constraints of the role of CSR (Corporate Social Responsibility) Banyan Tree Resort Bintanin building prosperity of the social environment communityLagoiKepulauan Riau. The design of this research is qualitative descriptive. The subject of this research is the key informant that isCSR (Corporate Social Responsibility) Manager Banyan Tree Resort Bintan and additional informants is community LagoiKepulauan Riau. Data collection techniques used were observation, documentation, in-depth interviews and document studies. Data analysis techniques refer to the theory expressed by John Elkington (2007). The results showed that CSR (Corporate Social Responsibility) Banyan Tree Resort Bintan plays an important role in building social welfare community lagoiKepulauan Riau through such as entrepreneurship and opening of employment, environment such as greening, nature conservation, energy use efficiently, and social such as education, training and compensation.Keywords : CSR, building prosperity of the social environment community